Mekanisme Akses Masyarakat Dalam Pemanfaatan Sumber Daya Hutan di Taman Nasional Lore Lindu - Lareke, Amir A; massiri, Sudirman Daeng; maiwa, Arman; ladiva, Ladiva (Fakultas Pertanian, Sains, dan Kesehatan, Universitas Timor, 2024)
The access that communities have to the forest is a major factor in maintaining a balanced use of forest resources. People's dependence on the forest is reflected in various aspects of their daily lives. However, when forest products are exploited without permission, the impact can be very damaging to the forest ecosystem. The purpose of this study was to analyze the mechanisms used by the community in obtaining, controlling and regulating their access to the use of forest resources around the Lore Lindu National Park area. The respondent sampling technique used is purposive sampling, which is a sampling method that is carried out deliberately or intentionally selected by researchers based on certain characteristics that are considered relevant to the research objectives. Where the population of people who utilize forest resources is 30 respondents who are sampled in this study. The data collection method used is a case study, where data collection is carried out through in-depth interviews and involved observations. The data collected was analyzed using access theory. The results showed that the Bobo Village community relies heavily on forest products for their daily lives and livelihoods, even though TNLL has been designated as a conservation area. In this case, the community has obtained forest resources for generations, but often uses unauthorized land in the TNLL area. Control and regulation efforts are carried out by TNLL management and village conservation management institutions to maintain the sustainability of the area. This research highlights the importance of systematic cooperation and regulation in maintaining the sustainability and function of TNLL in the midst of community dependence on natural resources. The community continues to access the TNLL area and continues to utilize forest resources around the area.